Divergences in the euro area: A cause for concern? - Nils Björkstén; Miika Syrjänen (Bank of Finland, 1999)
Evidence suggests that after a period of convergence in the early and mid 1990s, the euro area economies may have started diverging. As a consequence, the common monetary policy could become less well-suited for a number of countries.This paper studies the extent and severity of the recent divergences, and discusses the capacity of exposed countries to compensate for nationally suboptimal monetary conditions through other policy channels.As a step toward developing an analytical framework for monitoring intra-euro area developments, we present a "convergence barometer" to monitor divergences, and a Taylor rule based "monetary thermometer" to compare the common monetary policy to benchmark optimal policy for individual countries.A main conclusion is that policyrnakers at the euro area level should be concerned about divergences, since automatic stabilisers alone may not be enough to restore a healthy equilibrium to potential "outlier" countries.
URN:NBN:fi:bof-20140807227
Keywords: 330